2005
DOI: 10.1074/jbc.m411295200
|View full text |Cite
|
Sign up to set email alerts
|

Varied Mechanisms Underlie the Free Sialic Acid Storage Disorders

Abstract: Salla disease and infantile sialic acid storage disorder are autosomal recessive neurodegenerative diseases characterized by loss of a lysosomal sialic acid transport activity and the resultant accumulation of free sialic acid in lysosomes. Genetic analysis of these diseases has identified several unique mutations in a single gene encoding a protein designated sialin (Verheijen, F. W., Verbeek, E., Aula, N., Beerens, C. E., Havelaar, A. C., Joosse, M., Peltonen, L., Aula, P., Galjaard, H., van der Spek, P. J.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
73
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(89 citation statements)
references
References 45 publications
9
73
0
1
Order By: Relevance
“…3 E-G). Importantly, expression of the sialin mutant L22A-L23A, which reportedly is targeted to the plasma membrane (24,25), increased the currents by approximately twofold with either NO 3 − or SA in the external solution ( Fig. 3 H and I).…”
Section: Sialin Mediates Nomentioning
confidence: 93%
See 1 more Smart Citation
“…3 E-G). Importantly, expression of the sialin mutant L22A-L23A, which reportedly is targeted to the plasma membrane (24,25), increased the currents by approximately twofold with either NO 3 − or SA in the external solution ( Fig. 3 H and I).…”
Section: Sialin Mediates Nomentioning
confidence: 93%
“…To establish the link between sialin and nitrate transport, we examined the effect of two nonfunctional sialin mutants that have been associated with Salla disease (R39C) and ISSD (H183R) (23)(24)(25). Expression of each of these mutants in HSG cells induced dominant suppression of both NO 3 − and SA − currents without altering the current-voltage (I-V) characteristics (Fig.…”
Section: Assessment Of Sialin-mediated No 3 − Transport In Fibroblastmentioning
confidence: 99%
“…The lysosomal transporter sialin was first identified through genetic studies of the human free sialic acid storage disorders, Salla disease and infantile sialic acid storage disorder, a group of diseases in which the sialic acid N-acetylneuraminic acid (NANA) 2 and glucuronic acid (GlcUA) accumulate in lysosomes (1). These acidic sugars are normally transported out of the lysosome after they are released during degradation of glycolipids and glycoproteins.…”
mentioning
confidence: 99%
“…Moreover, it is frequently observed that mutations disturb targeting of the protein to the correct cellular organelle. For instance, sialin, another member of the SLC17 family, is a lysosomal sialic acid/H ϩ co-transporter and targeted to the plasma membrane when mutations are introduced into its dileucine motif (21,22). Because the VGLUT assay procedure is based on the assumption that the transporter is targeted to acidic organelles and that endogenous ATP fully energizes V-ATPase to drive the uptake, it is not certain whether this assay is valid for mutant VGLUT.…”
mentioning
confidence: 99%